Simulation of Wear in Involute Micro Gear - Shi Wankai; Wang Xu; Han Zhenhua; Liu Yin (Jixie chuandong)
In order to further study the microscopic wear mechanisms of micro gear,by using the classical Archard wear equation,combining with JKR（Johnson K L,Kendall K,Roberts A D） theory and GW（Greenwood and Williamson） rough surface model,a simulation model of the wear in micro gear is firstly established and the measures to reduce tooth wear are proposed.The simulation with considering the influence of single factor and multiple factor of surface attractive forces,surface roughness,the radius of curvature in asperity apex,material property etc.on tooth surface wear is carried out.The results show that an appropriate increasing in the surface roughness,reducing the radius of curvature in asperity apex,selecting the gear with larger parameter product value ηβσ which describing the rough surface,choosing the material which has a larger elastic modulus can alleviate wear and extend wear life.